PENGARUH ANGGARAN BERBASIS KINERJA DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KINERJA INSTANSI PEMERINTAH PADA KANTOR DINAS PEMERINTAH KABUPATEN BADUNG - Ni Made Kertiani; Ni Putu Ayu Kusumawati; Putu Cita Ayu (UNHI Press, 2020)
The purpose of this study was to determine the effect of performance-based budgeting and regional financial accounting systems on the performance of government agencies in government offices in Badung Regency. The population used in this study were all employees working in the Badung Regency Office as many as 1089 people. Determination of the sample using purposive sampling to obtain 102 people as samples. After testing the instrument and testing the classic assumptions, then the data analysis is performed using multiple linear regression analysis, determination, t test, and F test. The analysis showed that the effect of performance-based budgeting on the performance of government agencies obtained a regression coefficient of 0.133, tcount value of 2.291 and t test significance value of 0.024 <0.05, so that H1 was accepted, it can be concluded that performance-based budgeting has a positive and significant effect on the performance of government agencies in the Badung Regency Government Office. The influence of the regional financial accounting system on the performance of government agencies obtained a regression coefficient of 0.698, tcount of 14.181 and t test significance value of 0.000 <0.05, so H2 is accepted, it can be concluded that the regional financial accounting system has a positive and significant effect on agency performance government at the Badung Regency Government Office.